2022
DOI: 10.17957/ijab/15.1892
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phosgreen Fertilization on the Growth and Phosphorus Uptake of Lettuce (Lactuca sativa)

Abstract: The effect of Phosgreen fertilizer on the growth, development and biometric traits of lettuce was determined in comparison to superphosphate on two selected horticultural media. The aim of the experiment was to evaluate the effect of Phosgreen on the basis of the reaction of tested plants. Lettuce was grown on two horticultural media: mineral soil and deacidified peat. This study determined phosphorus content and uptake as a phosphorus fertilizer effect on different horticultural media. Lettuce developed and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…In our study, struvite fertilization did not have a more significant effect on seed yield and phosphorus uptake than that seen in other studies 15 , 34 , 35 but it did have an effect on seed phosphorus content. Despite the lack of significant differences, greater values of seed yield and P uptake can be attributed mainly to the greater amount of Mg contained in Crystal Green fertilizer and its synergistic effect on P uptake 36 .…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In our study, struvite fertilization did not have a more significant effect on seed yield and phosphorus uptake than that seen in other studies 15 , 34 , 35 but it did have an effect on seed phosphorus content. Despite the lack of significant differences, greater values of seed yield and P uptake can be attributed mainly to the greater amount of Mg contained in Crystal Green fertilizer and its synergistic effect on P uptake 36 .…”
Section: Discussioncontrasting
confidence: 78%
“…Struvite also contains some heavy metals, as wastewater contains a significant amount of such elements; however, these occur within acceptable limits, as has been proved in our own research 12 . Experimental data from various plant species proves that struvite fertilization results in similar plant yields to those achieved with mineral fertilization 7 , 8 , 12 15 .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Most agricultural elds are P-poor and are rapidly depleting P supplies, which is a serious global problem [23][24][25] . Balance disturbance of elements in the soil can change the dynamics of other nutrients in plant parts by affecting their uptake and assimilation 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In the system production of cactus pear, several authors reported that nitrogen and phosphorus fertilizing (N-P fertilizing) affect positively fruit yield and size in not scozzolaturated plants. Moreover, treatments providing high amounts of nitrogen and phosphorus affect more fruit yield and size than other treatments of fertilization [11,12,13,14,15,16,17,18]. Some other authors indicated that mineral fertilization of cactus pear improved fruit yield.…”
Section: Introductionmentioning
confidence: 99%